Rigging by the state apparatus: systemic electoral fraud in Mozambique jeopardizes the credibility of democracy and creates room for political violence - Nhamirre, Borges Joaquim Faduco (Frontiers in Political Science, 2025)
In Mozambique, systematic electoral fraud has persistently prevented the will of the electorate, as expressed at the ballot box, from being reflected in the selection of national leadership. This has resulted in recurrent post- electoral conflicts between the main opposition parties and ruling authorities, often addressed through political agreements and legal reforms aimed at preventing future irregularities. Although successive electoral reforms have improved transparency and expanded access to independent domestic and international observation, election rigging continues. Recent trends reveal an increasing reliance on the state apparatus—including legislative bodies, electoral commissions, the police, and the—judiciary to influence electoral outcomes. This article draws on a review of relevant literature, key informant interviews, and both direct and indirect observation to examine the evolution of electoral fraud in Mozambique. It demonstrates how fraudulent practices have become sophisticated to adapt to a society with growing access to information and heightened civic awareness. The paper argues that the systemic manipulation of electoral processes by state institutions has eroded the credibility of democratic institutions and may foster organized political violence, posing serious threats to peace and political stability.